KOMUNIKASI POLITIK DAN EKSISTENSI ADAT - Malik, Abdul (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2018)
In Banten, traditional elites who frequently appear in every political event besides religious leaders (kiai) and jawara are pemuka adat (community leaders) in Kasepuhan Banten Kidul. In the era of decentralization and regional autonomy and along with the implementation of direct elections and regional elections, the involvement of adat leaders by political power and power has also increased. Not only as spiritual advisers, but also as actors of political communication for the sake of certain political forces and powers. In the perspective of the theory of social action, the involvement of the adat leaders as political communicators is a form of social action or is also called a rational action that has a goal to achieve. This goal refers to two things. First, the role and involvement of the adat leaders in Kasepuhan Cisungsang as political communicators is based on the awareness of making changes in the community which is motivated by the marginalization and neglection of development in their region due to the regulation and impartiality of the government. Secondly, the role and involvement of adat leaders as political communicators has a meaning as an effort to uphold the existence of adat      due to marginalization and impartiality as well as an influence to government policies that can have positive implications for the development and welfare of the community, including in terms of legal recognition by the state in the form of regional regulations (perda).